The Evolving Role of Automation in Transportation: Human Factors Lessons Learned from the Different Modes. (September 2016) - Allahyar, Maryam; Becic, Ensar; Chappell, Sheryl; Fisher, Donald; Lohrenz, Maura; Monk, Chris; Philips, Brian
Automation is not only in our future, it is already here. This has long been the case for aviation (FAA). But it is increasingly the case for our highly connected systems of vehicles (NHTSA), highways (FHWA), and railroads (FRA). Clearly we must educate the operators about the capabilities and limitations of these new automated systems (NTSB). The purpose of this panel is to share, at this critical point in the development of automation, the knowledge that has been gained across the different modes of transportation about how best to develop systems that may help reduce the approximately 94% of crashes attributed to human error. The five presenters (Allahyar, Becic, Chappell, Monk, and Philips) come from the different modes and have been centrally involved in the efforts to understand the role of the human operator in automated systems. Active engagement with the audience is expected.